Trade uncertainty and U.S. bank lending - Ricardo Correa; Julian Di Giovanni; Linda S. Goldberg; Camelia Minoiu (Federal Reserve Bank of Atlanta, 2024)
This paper uses U.S. credit register data and the 2018-19 Trade War to study the effects of uncertainty on domestic credit supply. Exploiting differences in banks' ex-ante exposure to trade uncertainty, we find that increased uncertainty is associated with a broad lending contraction across their customer firms. This result is consistent with banks responding to uncertainty with wait-and-see behaviors, where more exposed banks curtail risky exposures, reduce loan maturities, and adjust loan supply along both intensive and extensive margins. The lending contraction is larger for more capital-constrained banks and has significant real effects, especially for bank-dependent firms.
Keywords: G21; F34; F42; 330; uncertainty; bank loans; trade finance; credit supply; trade war